Cell migration behavior regulation by nanopillars and oxide coating - Chang Liu; Chenyang Xue; Binzhen Zhang (AIP Advances)
The extracellular matrix provides a structural foundation for cells while also providing biophysical and biochemical signals that guide and influence cell migration. Previous studies have demonstrated that factors such as topography, material composition, and surface energy can significantly influence the migratory behaviors of cells. However, the relationship between surface energy and cell migration on various surfaces is not well understood. To investigate this, we fabricated polydimethylsiloxane (PDMS) platforms featuring nanopillars, as well as silicon oxide (SiOx) and titanium oxide (TiOx) surface coatings. The study examined the cells’ migration speed, morphology, and spreading in relation to the different surface properties and surface energies. Cells exhibited distinctive migration behaviors on the PDMS platforms with nanopillars and various surface coatings. In contrast to the flat PDMS, cells cultured on the SiOx and TiOx coatings exhibited less elongated morphologies, decreased mobility, and larger overall cell areas. Specifically, cells had the smallest cell elongation on the SiOx surface and the lowest migration speed on platforms coated with TiOx. In contrast, cells cultured on the nanopillar surface exhibited increased migration speeds, more elongated morphologies, and smaller overall cell areas. These findings suggest that cell migration behavior is obviously affected by the existence of nanopillars or the type of surface coating, which in turn is relevant to the surface energy of the platform. Elucidating the relationships between various surface properties, resulting cell migration behaviors, and overall surface energy could enable improved control over cell migration in a bionic platform designed to promote tissue regeneration and repair.